PREFERENSI PRODUSEN BABI GULING TERHADAP BABI BALI SEBAGAI BAHAN BAKU - I W., SUKANATA; PUTRI, B. R. T.; ., SUCIANI (Majalah Ilmiah Peternakan, 2018)
This study aims at observing the main attributes of bali pigs that prefer as a raw material suckling pig producer. Farmers have to know this thing in order to increase consumer satisfaction and their loyality. The data used interview and observation as primary data collected to fifty producers of suckling pig which is located in Bali. They were interviewed using questionnaires and analyzed with chi square and multiatribut Fishbein analysis. It showed that preferences of producers based on attributes of color, gender, body size and body condition significantly differ within 95% level of interest. Bali pig attributes that preferred by the producer as a raw material of roasted pig is bali pig with balck colour, sex of male, 10 up to 15 kg of body weight and fat body condition. The bali pig attributes considered by the producer in making decision to buy from the most consideration to the minimum such as body size, body condition, gender, and color. Body condition attribute was considered to be less satisfying for producers indicated with satisfaction score 2.9 from the maximum score of 5. So, it is important that farmers should pay attention to these attributes in the future.